Penyusunan Paket Wisata Budaya Berdasarkan Preferensi Wisatawan Yang Berkunjung ke Desa Wisata Penglipuran - Rizkika, Nia; Anggraini, Septia Putri; Rosidi, Farhan; Iwadah, Bawada; Perdana, Muhamad Ari (CV. ITTC INDONESIA, 2025)
This study aims to develop a culturally-based tour package by highlighting the local wisdom of Penglipuran Tourism Village, Bali, particularly through workshop activities on making Penjor and Canang Sari. The method used is a mixed method approach that combines qualitative and quantitative techniques through observation, interviews, and the distribution of questionnaires to tourists. The results show that the majority of tourist are interested in authentic cultural experiences, are around 20 years old, and are predominantly female. Based on the identification of tourist attractions, tourism facilities, and other services, a 2-day, 1-night tour package was designed with the theme “Spirit of Bali: Learning the Meaning Behind Penjor and Canang Sari”. This tour package combines natural, cultural, and man-made attractions with a structured schedule, including cultural workshops and educational visits. The tour package the pricing is determined based on the number of participants, with cost calculations considering profitability. This initiative is expected to enhance tourism products while contributing to the local economy and cultural preservation.